Optimal vitamin D plasma levels are associated with lower bacterial DNA translocation in HIV/hepatitis c virus coinfected patients. (24th April 2016) - García-Álvarez, Mónica; Berenguer, Juan; Jiménez-Sousa, Maria Ángeles; Vázquez-Morón, Sonia; Carrero, Ana; Gutiérrez-Rivas, Mónica; Aldámiz-Echevarría, Teresa; López, Juan Carlos; García-Broncano, Pilar; Resino, Salvador
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Vitamin D has been linked to the immune response modulation and the integrity of the intestinal mucosal barrier. Therefore, vitamin D might be involved in bacterial translocation related to HIV infection. Our major aim was to analyze the association between plasma levels of 25-hydroxy-vitamin D [25(OH)D] and bacterial 16S ribosomal DNA (bactDNA) in 120 HIV/hepatitis c virus (HCV) coinfected patients. Design: Cross-sectional study. Methods: Plasma 25(OH)D levels were quantified by enzyme immunoassay. The vitamin D status was defined as deficient (<25 nmol/l), insufficient (25–74 nmol/l), and optimal (≥75 nmol/l) plasma levels. Plasma bactDNA levels were measured by quantitative real-time PCR. For bactDNA levels the cutoffs used were as follows: low [<p25th (46 copies/μl)], moderate [p25th to p50th (78 copies/μl)], high [p50th to p75th (159 copies/μl)], and very high (>p75th). Results: Eighteen (15%) patients had 25(OH)D deficiency, 93 (77.5%) had insufficiency and nine (7.5%) had 25(OH)D optimal values. The bactDNA levels were lower in patients with 25(OH)D at least 75 nmol/l [37 copies/μl] than in patients with 25(OH)D insufficiency [84.2 copies/μl; P  = 0.042]. Conversely, low bactDNA levels (<p25th) were found in 66.7% of patients with 25(OH)D optimal levels, whereas bactDNA levels above p25th were found only in 11.1% of them ( P  = 0.029). The plasma 25(OH)D not less than 75 nmol/l was associated with low bactDNA levels (<p25th) [adjusted OR = 8.13 (95% confidence interval = 1.82; 36.67); P  = 0.006)]. The patients with optimal vitamin D status [25(OH)D ≥75 nmol/l] had lower plasma levels of CCL7 ( P  = 0.047) and basic fibroblast growth factor ( P  = 0.042). Conclusion: The optimal vitamin D status was associated with low bacterial translocation and inflammation in HIV/HCV coinfected patients.